Privatwirtschaftliche Baulanderschließung (Fraccionamientos) im Zuge der Stadterweiterung mexikanischer Städte aufgezeigt am Beispiel der Stadt Puebla/Pue - Popp, Kilian (ERDKUNDE, 1985)
Numerous authors have examined the structure and morphology of Latin American cities, but their research restricts itself to the macro-level of the city structure as well as to the meso-level of the inner and peripheral slum areas. Our research approach is con centrated on the legal framework of organized land development in urban areas. The study seeks to demonstrate the significance of land development projects in the private sector for the development of Mexican cities since 1940 and points out which social groups direct these relevant spatial processes. Using Puebla as an example, the ruling influence of urban elites who control the lucrative land development, due to their enormous economical, legal, and political influence is demonstrated. In the past few decades these elites have been the decision-makers concerning the location of residential and/or industrial areas. There fore it can be said that it is they who have determined the actual urban development. However, their methods lead to the loss of functioning city structures, to the increase of spatial disparities, and to further political tension within Mexico itself.